India's Growth Spillovers to South Asia - Masha, Iyabo (IMF Working Papers; Working Paper, 2012)
This study investigates the role of India's economy in explaining the observed growth in South Asia, taking into consideration other sources of growth endogenous to the countries in the region. Since a review of key variables indicates that India's bilateral trade and financial linkages with South Asian countries (SAC) are relatively weak, the paper analyses the spillover effects by focusing on growth more generally with India's growth as an explanatory variable. The results of the panel growth regressions suggest that India's growth has good explanatory power for growth in other SAC after 1995.